In Search of Early Time: An Original Approach in the Thermographic Identification of Thermophysical Properties and Defects. (17th February 2013) - Balageas, Daniel L.
Abstract : Active thermography gives the possibility to characterize thermophysical properties and defects in complex structures presenting heterogeneities. The produced thermal fields can be rapidly 3D. On the other hand, due to the size of modern thermographic images, pixel-wise data processing based on 1D models is the only reasonable approach for a rapid image processing. The only way to conciliate these two constraints when dealing with time-resolved experiments lies in the earlier possible detection/characterization. This approach is illustrated by several different applications and compared to more classical methods, demonstrating that simplicity of models and calculations is compatible with efficient and accurate identifications.